Fostering Inclusive Development: The Government's Role in Integrating a Gender Perspective: Mewujudkan Pembangunan dengan Perspektif Gender: Peran Pemerintah dalam Inklusivitas - Novitasari, Devi; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2023)
This research employs a descriptive qualitative method to analyze the government's role in promoting gender perspective in development within Sidoarjo Regency, Indonesia. Utilizing purposive sampling, the study draws upon role theory by Soerjono Soekanto, focusing on active, participatory, and passive roles. Findings reveal that the Sidoarjo Regency Government effectively advocates and socializes gender mainstreaming, demonstrating an active role. The government engages in education and motivation, encouraging broad societal participation, exemplifying a participatory role. However, a passive role is observed in limited active involvement in socialization activities. This research underscores the importance of government initiatives in fostering gender equality, offering insights applicable to global development discourse Highlight : Government Advocacy and Socialization: The study reveals the Sidoarjo Regency Government's effective advocacy and socialization efforts in promoting gender mainstreaming, reflecting an active role. Participatory Engagement: Through education and motivation, the government actively involves diverse societal levels, fostering a participatory role in advancing gender equality within development initiatives. Passive Role Observation: The research identifies areas where the government maintains a passive role, primarily limited to socialization activities, shedding light on potential areas for increased active involvement in gender-responsive development efforts Keywords: Gender-Responsive Development, Government Role, Sidoarjo Regency, Role Theory, Gender Mainstreaming